Mandated political representation and crimes against the low castes - Victoire Girard (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Mandated political representation over the last twenty years has had a different impact on the reporting of crime by the low castes than what is observed for the reporting of crime by women. I exploit the timing of the implementation of mandated political representation of the low castes to examine its effect on crime reports by these people. Mandated political representation of the low castes in India appears to affect the declaration of crime only for two very specific crime categories: identity-based crimes and murders. The increase in identity-based crimes (based on caste) is consistent either with better recording of existing crimes, or an increase in the incidence of committed crimes. The evolution of murders, which according to most specifications have increased after the implementation of political representation, is only consistent with an increase in incidence. This is all the more worrisome, given that the introduction of exclusive special courts, which were meant to further empower the low castes to report identity-based crimes, has not had the desired effect. A comforting observation is that crime disclosures do not increase during electoral years, contradicting the qualitative literature which points to incidents concerning reserved seats during elections. Nevertheless, mandated political representation has not had as strong an effect in giving voice to the low castes as has been documented earlier for women.
Keywords: D63; J15; O12; O53; 330; crime; justice; India; inequality; caste; political reservation; political quotas; discrimination